Modified Parabolic Extrapolation Based Maximum Power Point Tracking of Thermoelectric Generator for Dynamic Conditions - Rajendran, S (Institute of Electrical and Electronics Engineers Inc., 2024)
A thermoelectric generator (TEG) is a one of thermo electric conversion device that operates based on the heat difference between the two surfaces of a device. In a TEG, the power generation varies owing to various ambiences, sources, and loads. These variables make it difficult to draw available power from the device, leading to poor utilization of the TEG. To overcome these drawbacks, maximum power tracking technique (MPPT) can be employed in TEG. A modified PEMPPT scheme is developed to track the maximum power point (MPP) when there is a change in the operating conditions, and is based on a parabolic curve of the power current characteristics of the TEG. The proposed algorithm is developed by considering two features. First, the reduction in tracking time by a sample compared with the PEMPPT algorithm by considering a new shifted point as the first duty. Second, the sign of the voltage is checked to limit the voltage, current, and power by applying the next duties close to the MPP. The proposed system is simulated and experimentally verified using a laboratory prototype. The simulation and experimental results show that the tracking time of the proposed algorithm is almost 3/4th of PEMPPT. © 2017 CMP.